Empowering farmers with digital El Niño advisories: Insights from Malawi and Zambia - Chiduwa, Mazvita Sheila; Omondi, John O.; Masikati, Patricia; Ngoma, Hambulo; Nyagumbo, Isaiah (EIA, 2024)
Climate extremes, including droughts, floods, and cyclones, are becoming increasingly frequent, severe, and geographically extensive in Southern Africa, with devastating effects on populations heavily reliant on rain-fed agriculture and broader economies. Farmers urgently need guidance and support to build resilience against climate-related disasters. However, the national extension systems in the region lack adequate funding and the capacity to respond promptly and effectively during emergencies. This report analyzes a digital advisory campaign aimed at disseminating awareness and advisory messages to farmers during an El Niño event across Malawi and Zambia, leveraging Interactive Voice Response (IVR) technology accessible via basic, non-smart mobile phones. The campaign was rolled out in December 2023, prior to the start of the 2023/24 season. Our report builds on farmer feedback, particularly on how useful they found the campaign, their livelihood outcomes in the aftermath of the El Niño, and other notable trends in the data. The campaign reached over 1 million farmers in the two countries, with more than 90% of respondents finding the messages useful for awareness and preparedness. Both in Malawi and Zambia, radio emerged as the most popular channel for receiving extension messages. Moreover, results also confirmed that meteorological forecasts played a critical role in influencing farmers’ choices of crop and planting dates. For instance, dry spells of more than 21 days led to maize yield losses of 70-90%. Results further indicate that conservation agriculture and the adoption of drought-tolerant crops were the most popular mitigation measures employed by farmers. The findings suggest that Governments need access to appropriate information about the circumstances of their population to make informed decisions about how to efficiently extend support. Digital advisories provide an opportunity to gather real-time data on farm conditions and can be used to deploy support. Additionally, post-event analysis provides valuable evidence that can be used to enhance the design of future response interventions and reduce donor dependence.